Factors Associated with Postpartum Visits in the Work Area of the Polanharjo Health Center, Klaten, Indonesia - Novida Ariani; Rismaina Putri; Sonia Lahita Septianingrum (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research design uses cross sectional. A sample of 33 postpartum mothers in the working area of the Polanharjo Klaten Health Center. Of the 33 respondents, there were 20 respondents (60.6%) with incomplete postpartum visits and 13 respondents (39.4%) with complete postpartum visits. The highest level of education is junior high school with 16 respondents (48.5%), 19 respondents (57.6%) live near health care facilities, 23 respondents (69.7%) have low income, 21 respondents (63.6%) are supported family. Based on the Chi-Square Analysis, the p value of education level = 0.015, p distance from home to health facility = 0.011, p family income = 0.133, and p family support = 0.043. It can be concluded that there is a significant relationship between education level, distance from home to health facilities, family support and the number of postpartum visits.